2019
DOI: 10.3389/fbioe.2019.00319
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Hepatocellular Carcinoma by Intratumoral Injection of 125I-AA98 mAb and Its Efficacy Assessments by Molecular Imaging

Abstract: Objective: To investigate the therapeutic efficacy of intratumoral injection of 125I-AA98 mAb for hepatocellular carcinoma (HCC) and its therapy efficacy assessment by 99mTc-HYNIC-duramycin and 99mTc-HYNIC-3PRGD2 SPECT/CT imaging.Methods: HCC xenograft tumor mice models were injected intratumorally with a single dose of normal saline, 10 microcurie (μCi) 125I-AA98 mAb, free 125I, AA98 mAb, 80 μCi 125I-AA98 mAb, and 200 μCi 125I-AA98 mAb. 99mTc-HYNIC-duramycin and 99mTc-HYNIC-3PRGD2 micro-SPECT/CT imaging were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 33 publications
0
11
0
2
Order By: Relevance
“…A great deal of studies show that intratumoral injection of drugs has been proven to have a positive effect after many years of clinical research, can provide high drug concentrations at the tumor site with minimal exposure of nontarget tissues, and can prolong patient survival and improve quality of life [24][25][26]. Since Sugiura [27] first reported that Evidence-Based Complementary and Alternative Medicine PEI (percutaneous alcohol injection therapy) was adopted to treat liver cancer in 1983, the related research and clinical applications in the field have attracted wide attention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A great deal of studies show that intratumoral injection of drugs has been proven to have a positive effect after many years of clinical research, can provide high drug concentrations at the tumor site with minimal exposure of nontarget tissues, and can prolong patient survival and improve quality of life [24][25][26]. Since Sugiura [27] first reported that Evidence-Based Complementary and Alternative Medicine PEI (percutaneous alcohol injection therapy) was adopted to treat liver cancer in 1983, the related research and clinical applications in the field have attracted wide attention.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely accepted that angiogenesis is essential for tumor growth and invasion, and inhibition of angiogenesis is one of the important methods for treatment of cancer [25]. MVD reflects the tumor microvascular formation and the tumor aggression.…”
Section: Discussionmentioning
confidence: 99%
“…此外, PXR003抗体还能够缓解中枢神经炎症, 这是通过阻断Tc17 [328] 和Th17 [316,328] 细胞上CD146介导 的跨内皮迁移功能而实现的; 其后, PXR003被证实在 抑制前列腺骨转移方面具备良好的应用前景 [298] . AA98是目前研究最多、最深入的一株治疗性抗 体, 它识别新生血管 (188/193), 对正常血管结合较少(9/ 图 7 sCD146的病理学功能示意图 CD146, 如人 [366] 、恒河猴 [387] 、小鼠 [55] 、大鼠及鸡 [10] . 该抗体是本团队 [244] 用肿瘤细胞培养上清活化的HU-VEC细胞作为免疫原, 制备出的单克隆抗体(IgG2a).…”
Section: 体 该抗体靶向Cd146unclassified
“…型中均显示良好的治疗效果, 如肝癌 [366] 、骨肉瘤、胰 腺癌、卵巢癌 [119,279] 、宫颈癌 [219] 、肠炎 [368] 、多发硬 化症 [329] 、动脉粥样硬化 [337] 等. , 以及抑制卵巢癌 和黑色素瘤的转移和癌栓形成的作用.…”
Section: 抗体Aa98作为重要的研究工具 揭示了Cd146的unclassified
“…4 The accumulating evidence demonstrates the survival benefit of cancer patients from anti-angiogenic therapy, such as metastatic colorectal cancer, hepatocellular carcinoma, and others. 5,6 Epithelial ovarian cancer (EOC) ranks the first fatal disease in female reproductive malignancies. 7 Despite the advances in chemotherapy and surgery, the 5-year survival rate of advanced EOC patients is always less than 30% for several decades, due to drug resistance.…”
Section: Introductionmentioning
confidence: 99%